Health Care Coalitions as Response Organizations: Houston After Hurricane Harvey. (27th December 2017) - Upton, Lori; Kirsch, Thomas D.; Harvey, Melissa; Hanfling, Dan
Abstract: Health care coalitions play an increasingly important role in both preparedness for, response to, and recovery from large scale disaster events occurring across the United States. The actions taken by the South East Texas Regional Advisory Council (SETRAC) in response to the landfall of Hurricane Harvey, and the consequential flooding that ensued, serve as an excellent example of how health care coalitions are increasingly needed to play a unifying role in response. This paper highlights a number of the strategic planning, operational planning and response, information sharing, and resource coordination and management activities that were undertaken for the response to Hurricane Harvey. The successful response to this devastating storm in the Houston, Texas area serves as an example to other regions across the country as they work to implement the 2017-2022 health care capabilities articulated by the Department of Health and Human Services Office of the Assistant Secretary for Preparedness and Response. ( Disaster Med Public Health Preparedness . 2017;11:637–639)